2010
DOI: 10.1002/anie.201001275
|View full text |Cite
|
Sign up to set email alerts
|

B19: An Aromatic Wankel Motor

Abstract: The magic roundabout: The B19− cluster behaves like a molecular Wankel engine (see picture) in which the two concentric boron rings rotate in opposite directions. During the rotation the cluster remains planar owing to a marginal rotational energy barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 31 publications
7
118
1
Order By: Relevance
“…The most reasonables cheme is 12 rhombic 4c-2e s bonds alongt he outerB DR ribbon ( Fig-ure 3a). [47][48][49] People would even argue that the most important contribution to electron delocalization comes from s electrons. It is stressed that this schemei s an approximationb ecause s delocalization is known to be crucial in boron clusters.…”
Section: Computationaldetailsmentioning
confidence: 99%
“…The most reasonables cheme is 12 rhombic 4c-2e s bonds alongt he outerB DR ribbon ( Fig-ure 3a). [47][48][49] People would even argue that the most important contribution to electron delocalization comes from s electrons. It is stressed that this schemei s an approximationb ecause s delocalization is known to be crucial in boron clusters.…”
Section: Computationaldetailsmentioning
confidence: 99%
“…18,[27][28][29][30][31][32] first-principles methods. [28][29][30][31][32] In particular, first-principles molecular dynamics (FPMD) simulations demonstrated that the structural transformation of B 5 fragment between six-and seven-membered rings is an element process in isomerization of the B 40 fullerene. 18 The axially chiral B 39 − fullerenes possess a distinctive structural fluxionality: B 39 − hops between the C 3 and C 2 isomers with low energy barriers during FPMD simulations at 300K.…”
Section: -9mentioning
confidence: 99%
“…Jiménez-Halla et al published the observation of a B 19 − aromatic wankel motor [9]. Internal rotation in B 13 + was studied with chemical bonding analysis [10], and activated with a laser [11].…”
Section: Introductionmentioning
confidence: 99%